Natural Compounds Promoting Weight Loss: Mechanistic Insights from the Point of View of the Medicinal Chemist - Ribaudo, Giovanni; Ongaro, Alberto; Zagotto, Giuseppe (Natural Products Journal, The, 2019)
Background: The adipose tissue acts as a buffer storing and releasing energy according to the needs of the body. In a non-physiological context, the development of obesity is related to an unbalance in the homeostasis between calories intake and energy consumption. Objectives: This review focuses on the natural compounds and the herbal extracts used in dietary supplements that are claimed to suppress appetite and promote weight loss. Such compounds or mixture of compounds act through different molecular mechanisms that will be discussed from the point of view of the Medicinal Chemist. The reader will be also briefly updated on the recurring adulteration cases that affect the market of dietary supplements. Methods: The bibliographic research was performed using online scientific databases (PubMed, Reaxys, Scopus) exploiting different keywords and logical operators to lay the bases for an accurate, quality criteria-based literature update. Results: Over 70 papers were selected for the preparation of this review, preferring the reports that are supported by pre-clinical and clinical data. Conclusion: Activity on adrenergic receptors, modulation of adenosine receptors, interference with glucose and lipid metabolism, regulation of adipocyte cell cycle and inhibition of phosphodiesterases are the main molecular mechanisms by which different natural compounds act in promoting weight loss.
Keywords: Weight loss